Analysis Of Drawing Methods Among Selected High School Students In Jordan - Mayyas, Asma' Nawaf Abdallah (2024)
Drawing, as one of the art education domains, contributes to developing the individual's capabilities and skills, especially students, in all educational stages. Jordanian schools’ teaching of drawing is based on traditional foundations that rely on memory. However, there are studies that indicated the importance of using visual aids (photography image) to create drawing. This study aims to investigate the difference between the two methods of creating students’ drawings.